The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.3390/ijerph15071484
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Stakeholder Perspectives of Factors That Influence Contact Centre Call Agents’ Workplace Physical Activity and Sedentary Behaviour

Abstract: Contact centre call agents are highly sedentary at work, which can negatively affect cardio-metabolic health. This qualitative cross-sectional study explored factors influencing call agents’ workplace physical activity (PA) and sedentary behaviour (SB), and perspectives on strategies to help agents move more and sit less at work. Semi-structured interviews and focus groups with call agents (n = 20), team leaders (n = 11) and senior staff (n = 12) across four contact centres were guided by the socio-ecological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(35 citation statements)
references
References 53 publications
(114 reference statements)
2
24
0
Order By: Relevance
“…Identifying, and addressing barriers and enablers as part of the intervention development process is also consistent with guidance from the Medical Research Council [16] and supports the development of more effective interventions [15]. To date, only a small number of studies have reported barriers and enablers to workplace sitting interventions as a first step to intervention development [1719]. More frequently, qualitative studies have explored barriers and enablers to sitting less at work as a standalone study, without explicitly stating that these findings will then be used to inform the development of interventions [2022].…”
Section: Introductionmentioning
confidence: 76%
“…Identifying, and addressing barriers and enablers as part of the intervention development process is also consistent with guidance from the Medical Research Council [16] and supports the development of more effective interventions [15]. To date, only a small number of studies have reported barriers and enablers to workplace sitting interventions as a first step to intervention development [1719]. More frequently, qualitative studies have explored barriers and enablers to sitting less at work as a standalone study, without explicitly stating that these findings will then be used to inform the development of interventions [2022].…”
Section: Introductionmentioning
confidence: 76%
“…Team leaders are perceived as pivotal in changing call agent perceptions of workplace PA and SB [18] and are frequently utilised in workplace interventions [61,62]. Accordingly, to provide call agents in the present study with interpersonal support from their team leader, all team leaders were invited to participate, with only call agents in the team of an interested and eligible team leader subsequently invited to participate.…”
Section: Discussionmentioning
confidence: 99%
“…Factors contributing to low PA and high SB at work among call agents are multifaceted and include high productivity requirements, sedentary working cultures and sitting-based workstations [18][19][20]. In contrast to other sectors of desk-based workers (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Contact centres (also known as call centres) are associated with higher levels of sedentary behaviour than other office-based workplaces [4,24,25]. Employees typically spend up to 90% of their working day sitting down [24].…”
Section: Introductionmentioning
confidence: 99%
“…Contact centres (also known as call centres) are associated with higher levels of sedentary behaviour than other office-based workplaces [4,24,25]. Employees typically spend up to 90% of their working day sitting down [24]. The technology used by staff in contact centres prevents them from regularly leaving their desk and many call handlers often report stressful work environments due to low workplace autonomy, strict supervision of individual performance and commission-based salary systems [26].…”
Section: Introductionmentioning
confidence: 99%